The Simulation Analysis on the Transient Process of Transformer. Issue 3 (October 2020) - Zhang, Peng; Wang, Yue; Lan, Sen; Zhang, Hongda; Zhang, Dewen; Liang, Jianquan
Abstract: Power transformer is one of the important equipment in the power grid, we must ensure its reliable operation. To achieve that goal, the insulation property of power transformer must be fine, for its breakdown mainly caused by the insulation damage. When the power transformer suffered from the lightning surges, the windings insulation is damaged easily, so we should optimize and design on the power transformers windings insulation structure. Firstly, the computational methods of the inductance, capacitance and the resistance parameter were introduced in this paper, then the inductance, capacitance and the resistance parameters of a SFP-180000/220 three-phase transformer were calculated. Based on the equivalent circuit of transformer, the circuit model in the Matlab was established and simulated when the neutral is grounded or insulated respectively. The relevant initial potential distribution, the oscillating potential distribution, and the final potential distribution were gotten by the simulation. Finally, the characteristics of each potential distribution were analysed, which could provide some references to the insulation structure design for transformers.